2015
DOI: 10.4253/wjge.v7.i7.702
|View full text |Cite
|
Sign up to set email alerts
|

Endotherapy of leaks and fistula

Abstract: Perforations, leaks and fistula involving gastrointestinal (GI) tract are increasing encountered in clinical practice. There is a changing paradigm for their management with surgical approach being replaced by conservative approach including endoscopic therapy. Clips (through the scope and over the scope) and covered stent are front runners for endotherapy for GI leaks and fistula. Over the scope clips introduced recently, can treat larger defects compared to through the scope clips. Covered stents are suited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 75 publications
0
51
0
1
Order By: Relevance
“…The surgical management of gastrointestinal tract perforations is now often replaced by conservative therapy [12]. For example, Merchea et al reported that non-operative management of EGD-associated upper gastrointestinal perforation can be successful when there is no evidence of contrast extravasation or free fluid on radiographic studies [13].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical management of gastrointestinal tract perforations is now often replaced by conservative therapy [12]. For example, Merchea et al reported that non-operative management of EGD-associated upper gastrointestinal perforation can be successful when there is no evidence of contrast extravasation or free fluid on radiographic studies [13].…”
Section: Discussionmentioning
confidence: 99%
“…Invasive methods are commonly used to treat fistulas and complications due to anastomotic leakage that develop after surgery for many benign and malignant GI diseases, which previously had only one treatment [5][6][7][8][9][10][11][12]. Because of the high morbidity and mortality of patients with a fistula and/or anastomotic leakage, the search for treatments has continued due to the lack of a demonstrably effective method.…”
Section: Discussionmentioning
confidence: 99%
“…Today, surgery is still used, but less frequently due to developments in endoscopic technology and assistant's tools. The success of treatments methods that are less invasive and easier than surgery has increased, and reduced complications from these methods have decreased the requirement for surgery remarkably in recent years [5][6][7][8][9][10][11][12]. In this study, we share our experience of patients who received continuous intraluminal aspiration to treat a fistula and anastomotic leakage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, admission in an intensive care unit with resuscitation facilities, such as emergency airway equipment and respiratory support should be considered for such patients. [12] Surgical treatment is an important option in many cases, but a non-operative approach should be preferred whenever the clinical situation permits a less invasive approach. [13] Non-operative approaches include endoclipping or endoscopic stenting.…”
Section: Discussionmentioning
confidence: 99%